Concentric and Eccentric Force Changes with Elastic Band and Isotonic Heavy Resistance Training: A Randomized Controlled Trial - Eric Folkins; Sidharth Sahni; John Ryan; Stacey Wooden; Gina Bushby; Christian Radzinski (North American Sports Medicine Institute, 2021)
# Background Inclusion of resistance training as part of a general fitness program to improve health, and lower risk of disease and injury is well established. Two common options to improve strength are elastic bands and weights. Comparison between elastic bands (as the sole resistance) to isotonic strengthening for concentric and eccentric strength outcomes following the use of low repetitions/heavy resistance has not been reported. # Hypothesis/Purpose The purpose was to examine the effects of a four-week isotonic low repetitions/heavy resistance strengthening program compared to a low repetitions/heavy resistance elastic band strengthening program on shoulder external rotation, hip abduction, and elbow flexion concentric and eccentric isokinetic force production in college aged untrained females. # Study Design Randomized Trial # Methods Twenty healthy females performed pre-and-post isokinetic (60 degrees/second) concentric/eccentric testing of the elbow flexors, shoulder external rotators, and hip abductors. Participants were randomly assigned to a four-week independent low repetitions/heavy resistance strengthening program performed with either elastic bands or isotonic exercises. # Results A significant (p < 0.05) effect of time was found for eccentric elbow flexor and concentric and eccentric hip abduction force production in the elastic band group with post-test values greater than pre-test values. A significant (p < 0.05) effect of time was found for elbow flexor concentric and eccentric force production in the isotonic group with post-test values greater then pre-test values. No significant (p>0.05) effect of time was found for shoulder external rotator concentric and eccentric forces for both groups, the isotonic group's hip abduction concentric and eccentric force production and elastic band group's elbow flexion concentric force production. No significant effect of intervention (p >0.05) on concentric or eccentric elbow flexors, shoulder external rotators, or hip abductors force production was found, with pre-test and post-test values being similar between groups. # Conclusion Health care practitioners and coaches can consider the prescription of a heavy resistance training program with elastic bands or isotonic exercises for an independent exercise program and expect similar concentric and eccentric muscle force changes. # Level of Evidence Level 2b